Volume 11: Systems, Design, and Complexity 2014
DOI: 10.1115/imece2014-39959
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics-Based Prototyping Strategy Formation: Development and Testing of a New Prototyping Planning Tool

Abstract: This work seeks to introduce and evaluate effects of a novel method for designing prototyping strategies. This newly developed heuristics-based tool guides designers in planning a prototyping strategy based on answers to Likert-scale questions that embody empirically validated heuristics. We created this tool to augment prior work in the development of prototyping planning methods. The new tool guides designers through six critical prototype strategy choices: (1) How many concepts should be prototyped? (2) How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…Techniques guide the embodiment of a prototype. Table 2 highlights a mapping from common techniques, 'How' , to the outcomes that they directly support, 'Why' (Camburn et al 2013a(Camburn et al ,b, 2014Dunlap et al 2014). The corollary process objectives of reducing cost, and reducing time are included here.…”
Section: A Framework For Design Prototyping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Techniques guide the embodiment of a prototype. Table 2 highlights a mapping from common techniques, 'How' , to the outcomes that they directly support, 'Why' (Camburn et al 2013a(Camburn et al ,b, 2014Dunlap et al 2014). The corollary process objectives of reducing cost, and reducing time are included here.…”
Section: A Framework For Design Prototyping Strategiesmentioning
confidence: 99%
“…Empirical studies show that teams iterating on a design significantly outperform teams without iteration, based on the evaluation of self-efficacy and design requirement satisfaction (Dow, Heddleston & Klemmer 2009;Camburn et al 2013aCamburn et al ,b, 2014Dunlap et al 2014). It has also been shown that knowledge of this effect can induce the use of iteration, compared to a control (Dunlap et al 2014).…”
Section: Iterative Prototypingmentioning
confidence: 99%
“…To increase the efficiency and effectiveness of prototype practice, researchers have proposed multiple prototyping methods and strategies from the Prototype for X (PFX) framework to a strategic design prototyping methodology that includes seven prototyping techniques (Camburn et al, 2015). Please refer to Menold's dissertation for an extensive review of current prototyping strategies , including these additional references (Camburn et al, 2017a;Christie et al, 2012;Hamon, 2017;Moe et al, 2004;Dunlap et al, 2014). Many of these strategies have been tested with student designers and are helpful in guiding them through prototyping practices, while also teaching fundamental principles about the importance of prototypes.…”
Section: The Need For the Prototyping Canvasmentioning
confidence: 99%
“…Many strategies aim to minimize the resources used to maximize the desired outcome. This was based on the following literature: Menold et al, 2017;Menold et al, 2018;Camburn et al, 2015;Camburn et al, 2017a;Christie et al, 2012;Hamon, 2017;Moe et al, 2004;Dunlap et al, 2014). On the canvas, this motivates the creation of three categories: "Building Plan", "Testing Plan", and "Insights."…”
Section: Synthesizing Prototyping Literature Into Prototyping Canvas V1mentioning
confidence: 99%
See 1 more Smart Citation